2017
DOI: 10.1016/j.chemosphere.2016.09.099
|View full text |Cite
|
Sign up to set email alerts
|

Pentachlorophenol affected both reproductive and interrenal systems: In silico and in vivo evidence

Abstract: h i g h l i g h t s g r a p h i c a l a b s t r a c tThe effects of PCP on steroid system were studied by in silico and in vivo assays.In silico results indicated interacting potency with steroid receptors by PCP. PCP caused adverse effects on reproductive and interrenal system in rare minnow. The HPG/I axis of rare minnow showed different response at 14th and 28th day.a r t i c l e i n f o The present study investigated the effects on reproductive and interrenal system by pentachlorophenol (PCP) using in sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…75 Similarly, transcriptional changes of cyp11a, hsd17b, and hsd3b were found in vertebrates exposed to other chemicals, accompanied by alterations in sex hormones. 75,76 The aromatase enzyme cytochrome P450 family 19 (CYP19) encoded by two isoforms catalyzes the final step of estrogen biosynthesis in fish (Figure 6). Two CYP19 isoforms, cyp19a and cyp19b, are mainly expressed in the ovary and brain, respectively, and regulate the gender differentiation and the reproductive behavior and cycle of most teleost fish through the production of E2.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…75 Similarly, transcriptional changes of cyp11a, hsd17b, and hsd3b were found in vertebrates exposed to other chemicals, accompanied by alterations in sex hormones. 75,76 The aromatase enzyme cytochrome P450 family 19 (CYP19) encoded by two isoforms catalyzes the final step of estrogen biosynthesis in fish (Figure 6). Two CYP19 isoforms, cyp19a and cyp19b, are mainly expressed in the ovary and brain, respectively, and regulate the gender differentiation and the reproductive behavior and cycle of most teleost fish through the production of E2.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, the upregulation in cyp11a and hsd3b expression in male fish following boscalid treatment may have helped stimulate the synthesis of E2, but the downregulation of hsd17b expression in female zebrafish may have contributed to diminished E2 synthesis. Due to the decline of E2 concentrations in females, we speculated that the increased expression of cyp11a and hsd3b might be a negative feedback response within the HPGL axis . Similarly, transcriptional changes of cyp11a , hsd17b , and hsd3b were found in vertebrates exposed to other chemicals, accompanied by alterations in sex hormones. , …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The study of the knockout of ER genes in zebrafish revealed that ERα is crucial for fertility. Accordingly, the ERα-mediated pathway is a classical pathway and the most important pathway for EDCs to exert endocrine-disrupting effects. In the study presented here, we aimed to determine the interactions of MePTs and their degradation products with ERα, using a combination of in vitro , in vivo , and in silico approaches. This study provides a direct target for reproductive endocrine disruption of MePTs and their degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…At lower concentrations more typically found in the environment, pentachlorophenol may have adverse effects on the reproductive and inter-renal systems of exposed fish. Fish exposed to environmentally relevant concentrations of pentachlorophenol for 28 days showed changes in steroid hormone levels in plasma, inhibition of spermatogenesis in male fish, and degeneration of ovaries in female fish (Yang et al 2017 ). Species sensitivity distributions provide helpful information about the relative toxicity of pentachlorophenol to various aquatic species (Jin et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%